Coherent enhancement of collection of light from linear ion crystals - Thuy Dung Tran; Daniel Babjak; Artem Kovalenko; Kratveer Singh; Tuan Minh Pham; Petr Obšil; Adam Lešundák; Ondřej Číp; Lukáš Slodička (npj Quantum Information)
Abstract The efficient detection of light from trapped ions in free space is paramount for most of their applications. We propose a scheme to enhance the photon collection from linear ion strings. It employs the constructive interference of light scattered from ions along the axial direction in linear Paul traps. The coherent enhancement of photon collection is numerically optimized for a range of feasible spatial angles and realistic ion positions in a single harmonic Coulomb potential. Despite the large mutual distance of scatterers on the order of many wavelengths of scattered light, the experimental tests presented confirm the feasibility of enhancements by a factor of 3.05 ± 0.09 with a crystal of nine 40Ca+ ions. The proposed collection geometry is intrinsic to diverse linear ion trap designs, and the methodology can be directly applied to an observation of scattering from ion crystals prepared in collective electronic excitations.